Haloperidol-induced changes in neuronal activity in the striatum of the freely moving rat - Yael, Dorin; Zeef, Dagmar H.; Sand, Daniel; Moran, Anan; Katz, Donald B.; Cohen, Dana; Temel, Yasin; Bar-Gad, Izhar (Frontiers in Systems Neuroscience, 2013)
The striatum is the main input structure of the basal ganglia, integrating input from the cerebral cortex and the thalamus, which is modulated by midbrain dopaminergic input. Dopamine modulators, including agonists and antagonists, are widely used to relieve motor and psychiatric symptoms in a variety of pathological conditions. Haloperidol, a dopamine D2 antagonist, is commonly used in multiple psychiatric conditions and motor abnormalities. This article reports the effects of haloperidol on the activity of three major striatal subpopulations: medium spiny projection neurons (MSNs), fast spiking interneurons (FSIs) and tonically active neurons (TANs). We implanted multi-wire electrode arrays in the rat dorsal striatum and recorded the activity of multiple single units in freely moving animals before and after systemic haloperidol injection. Haloperidol decreased the firing rate of FSIs and MSNs while increasing their tendency to fire in an oscillatory manner in the high voltage spindle (HVS) frequency range of 7-9 Hz. Haloperidol led to an increased firing rate of TANs but did not affect their non-oscillatory firing pattern and their typical correlated firing activity. Our results suggest that dopamine plays a key role in tuning both single unit activity and the interactions within and between different subpopulations in the striatum in a differential manner. These findings highlight the heterogeneous striatal effects of tonic dopamine regulation via D2 receptors which potentially enable the treatment of diverse pathological states associated with basal ganglia dysfunction.